POLLUTION LOAD (TSS, DO, BOD, AND COD) AND THE KALIYASA RIVER POLLUTION INDEX IN CILACAP DISTRICTS - Nilna Almuna Rizqi; Haeruddin Haeruddin; Siti Rudiyanti (Universitas Teuku Umar, 2021)
The Kaliyasa River was one of the many rivers in Cilacap Country. The River Kaliyasa is physically close to populations and industries that produce a wide range of products, making it a great potential for receiving both domestic and industrial wastes. The study was carried out in Oktober-November 2020 with four sample viewing points before the wastewater output, the wastewater outlet, at exactly the time of the wastewater output, and after the wastewater output. The sampling was done three times every two weeks. Based on this study, calculations indicate that the average value of the pollution load from the wastewater outlet was staggering at 32.661,60 kg/day. The average price of the pollution burden from the station after the wastewater output was produced a value of 15.945,92 kg/day. Average TSS, DO, BOD, and COD variables have already surpassed the second of class river quality. The Kaliyasa River pollution index is obtained that according to TSS, DO, BOD, and COD variables measured indicate IP Numbers in level 6, which include 6,16 of moderate pollutants. Keywords: Comparisons with Water Quality, Load Of River Pollution, Pollution Index